Supporting Proportional Reasoning Through Technology Integration in Mathematics Learning - Lutfi, Ahmad; Nurjanah, Nurjanah; Martadiputra, Bambang Avip Priatna; Jupri, Al (LPPM Universitas Pendidikan Mandalika, 2024)
This study aims to analyze the role of technology in facilitating the development of students' proportional reasoning skills in mathematics learning. This study used the systematic literature review method with a qualitative approach. Documents on the Scopus database were analyzed according to the research objectives using the PRISMA 2020. Thematic analysis was applied to all documents included in the search results. The results of this study indicated that there were 18 documents found that addressed the chosen topic-first in 2006, with 2015 being the most productive year discussing this topic. The technologies used to facilitate the development of proportional reasoning skills are Flash/ActionScript 3 programs-dominated, robotics, web-based learning, interactive touchscreen tablet application (MIT-Ext)-ordered by document quantity, virtual reality (VR), GeoGebra, video games, and augmented reality (AR). Quantitative, qualitative, and mixed-method approaches were used in almost equal parts. Junior high school was the most researched level of this topic, but no research has been conducted at the senior high school level. The most productive country to research this topic was the Netherlands. The results of this study were expected to provide practical benefits for teachers and future research.